(untitled) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2017)
Growing modern hybrids in narrow plant spacing together with nitrogen and herbicide application gives an advantage to maize crops over weeds. The aim of the present investigation was to evaluate the effect of nitrogen form, maize row spacing and herbicide treatment on weed and maize biomass and water usage, as well as maize yield. The investigation was conducted at the Maize Research Institute Zemun Polje, Belgrade during 2014-2016. A field experiment was set up as a split-split-plot block design with four replications. The maize hybrid ZP388 was planted, and a standard and a slow-release form of urea were applied. For each N source, maize was grown at two row spacings: narrow of 50 cm, and standard of 70 cm, while weed control treatments included: C - without herbicide application, T - application of a pre-emergence mix of herbicides. Sowing was done in the second decade of April, 2014, 2015 and 2016. Six weeks after herbicide application, the fresh biomass of weeds uprooted from 1 m2 and aboveground biomass of ten crop plants per plot were measured together with dry matter after drying in a laboratory oven. Water content (%) in weed and maize plants was calculated as a relation between fresh and dry biomass. Maize yield was measured at the end of each growing season and calculated with 14% of moisture. All data were processed by ANOVA. The fresh and dry biomass of weeds were significantly (P>0.05) higher in untreated control than in the treated variant, while differences in water content were not significant between the two treatments. Row spacing and urea form did not cause significant differences in weed parameters. Related to this, maize fresh and dry biomass, as well as water content, were higher in herbicide-treated variants than in control but differences were insignificant. Maize biomass was somewhat higher in 50 cm rows and after application of the slow-release urea fertilizer. Yield was higher from 70 cm rows and after application of the slow-releasing urea and the herbicides.